SiC/HfB2-based ceramic/SiC multilayer coating to protect C/C composites against oxidation at medium and high temperatures for long-life service. (June 2022) - Zhu, Xiaofei; Zhang, Yulei; Zhang, Jian; Su, Yangyang; Chen, Ruicong; Zhang, Pei
Abstract: A dense SiC/HfB2 -based ceramic/SiC multilayer coating was designed on C/C composites by a combined technique of pack cementation, slurry brushing-pressureless reaction sintering and chemical vapor deposition. The coating can protect C/C composites against oxidation at 1473 K for 544 h, 1573 K for 597 h and 1773 K for 382 h. Such good performance was ascribed to the synergistic oxidation resistance of three layers. The cracks were healed by the borosilicate glass generated from the oxidation of HfB2 -based ceramic intermediate layer at medium temperatures, and covered by SiO2 glass produced from the oxidation of SiC outer layer at high temperatures. Highlights: The multilayer coating composed of HfB2 -based ceramic internmate layer and two SiC layers is designed by a combined technique. The dense HfB2 -based ceramic internmate layer is prepared by introducing MoSi2 and resin carbon as reaction sintering additives. The cracks are healed by the borosilicate glass at 1473 K and SiO2 glass at 1773 K during oxidaiton, respectively. The coating can protect C/C composites against oxidation at medium and high temperatures for long-life service.